1975
DOI: 10.1073/pnas.72.12.5145
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in envelope structure of heptose-deficient mutants of Escherichia coli as revealed by freeze-etching.

Abstract: The surface of freeze-etched E. coli strain GR467, a heptose-deficient ("deep rough") mutant derived from CR34, was studied by electron microscopy. The outer membrane of GR467 has an increased ratio of phospholipid to protein, mainly due to a decreased protein content. Freeze-etched CR34 showed structural features indistinguishable from wild-type E. coli, i.e., the primary cleavage occurring in the inner membrane with only minor appearances of cleavage within the outer membrane. In contrast to this, in mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…We would also like to point out that the frequent fracturing of the cells through the OM differs from that found by other workers (3,26) and is caused by the high concentration of glycerol (30%, vol/vol) used in their preparation (Lounatmaa and Nanninga, in preparation). With this method, the cell wall of smooth S. typhimurium fractures through the OM much more easily than when lower concentrations of glycerol are used.…”
Section: Discussionmentioning
confidence: 59%
“…We would also like to point out that the frequent fracturing of the cells through the OM differs from that found by other workers (3,26) and is caused by the high concentration of glycerol (30%, vol/vol) used in their preparation (Lounatmaa and Nanninga, in preparation). With this method, the cell wall of smooth S. typhimurium fractures through the OM much more easily than when lower concentrations of glycerol are used.…”
Section: Discussionmentioning
confidence: 59%
“…This could account for the low level of complementation with HldA alone. SAL1 was also more sensitive that K56-2 to treatment with novobiocin and SDS (data not shown), which indicated that this mutant exhibits a deeprough LPS phenotype (2,51).…”
Section: Resultsmentioning
confidence: 97%
“…When overlying lipid bilayers are freeze cleaved, the fracture plane passes preferentially through the membrane with the lower protein/phospholipid ratio. For this reason, fractures in typical gram-negative bacteria rarely occur through the protein-rich, phospholipid-poor OM (9,32). In contrast to the OMs of gram-negative bacteria, the B. burgdorferi OM contained the preferred plane of cleavage, and this was explained by the significantly higher particle density of the B. burgdorferi CM.…”
Section: Discussionmentioning
confidence: 99%